IMPLEMENTASI PROGRAM LITERASI DAN KIR (KARYA ILMIAH REMAJA) DALAM MENCAPAI MUTU DI - Arthano, Arthano Arthano (Inspirasi Manajemen Pendidikan, 2018)
Nowadays, the world becomes more dynamic and competitive and we need quality generation. As educational service provider, schools actively play a role to create quality generation. The implementation of school?s major program is absolute requirement to achieve school?s quality and to create quality generation. This research aimed to describe and analyze; (a) Major programs in achieving quality at Al-Hikmah Senior High School of Surabaya; (b) Strategy of implementation of major programs to achieve quality at Al-Hikmah Senior High School of Surabaya; and (c) Participation of students? guardian in the implementation of major programs to achieve quality at Al-Hikmah Senior High School of Surabaya. This research used qualitative approach and case study design. The data of this research was collected by using interview, observation and documentation. The data that had been collected was then analyzed by using descriptive analysis through data condensation, data interpretation and conclusion drawing. To test the validity of the data, the researcher used technique which covered credibility, transferability, dependability and conformability. The result of this research showed that: (1) Al-Hikmah Senior High School of Surabaya had several major programs such as literation program (CALISA) and Teenager?s Scientific Paper which were aimed to achieve quality based on vision and mission which were stated on quality policy and specifically stated on school?s quality target. (2) The strategy of implementation of major programs at Al-Hikmah Senior High School of Surabaya covered the implementation of literation program (CALISA) and implementation of Teenager?s Scientific Paper which had some stages, problems and solution. (3) The roles of students? guardian in implementing literation program and Teenager?s Scientific Paper were granting permission, providing moral and financial support and actively participating on AKSIO (Al-Hikmah Science and Social Expo). Keywords: program to achieve quality, strategy of program implementation, role of students? guardian